A numerical study of the impacts of outdoor air intake and air changes per hour on the trichloramine concentrations in a swimming pool enclosure - Proulx, H.; Hallé, S. (Frontiers in Built Environment, 2022)
Trichloramine (NCl3) is a disinfection by-product commonly found in the water and air in indoor swimming pools. The gas is associated with chronic diseases such as asthma, and often causes eye and skin irritation. Due to its higher density than air, NCl3 tends to accumulate close to the water surface and above the deck. Mixing ventilation is the main ventilation strategy used in aquatic centers to maintain the NCl3 concentrations at an acceptable level. However, swimming pool halls are known to be significantly energy-intensive, thanks mostly to water evaporation from the basin. Consequently, building codes recommend maintaining a low air speed above the pool and deck to minimize evaporation and to ensure swimmers’ thermal comfort. If trichloramine levels are suspected to be too high, pool managers will favor increasing the number of Air Changes per Hour (ACH) while limiting the Outdoor Air (OA) intake. However, mechanical filtration systems are not designed to remove NCl3 from the airflow. Since its concentration cannot be measured directly, ventilation system parameters are often based on minimum recommendations set out in building codes, and may vary in operation according to the CO2 levels in the extracted air, irrespective of the NCl3 level and its accumulation behavior. It remains unknown how the OA intake ratio affects NCl3 levels in breathing zones. This paper carries out a numerical investigation of the impacts of the OA and the ACH on NCl3 concentrations in a swimming pool hall in Montreal (Canada). Results show that the minimum recommendations (OA intake and ACH) by ASHRAE are not sufficient to eliminate NCl3 accumulation and stratification in the lower breathing zones. Moreover, air recirculation mostly affects the breathing zones of standing occupants on decks and of lifeguards, but has a smaller impact on the breathing zones of swimmers or people sitting on the deck. Eliminating air recirculation does not guarantee better air quality in terms of NCl3 in these breathing zones. The findings for the complex under study may be used to guide similar research in other aquatic centers and for the continuous development of building codes and air quality standards.